Targeted Advertising and Protection of Personal Data: Implementation in the Conditions of European Integration (Law, State and Telecommunications Review, 2024)
[Purpose] To conduct a comprehensive analysis of the essence, types of targeted advertising, and features of personal data protection in the context of using targeted advertising with the aim of aligning Ukrainian legislation with the requirements of the European Union. In particular, the study aims to analyze the nature of advertising and the role of targeted advertising in the modern world, identify the main advantages and disadvantages of using targeted advertising, characterize different types of targeted advertising (such as contextual advertising, advertising in social networks, actually targeted advertising, and retargeting), analyze problematic issues related to the protection of personal data of users during the use of targeting technologies in Ukraine, describe key regulatory documents in the field of personal data protection in the online space that is active in the European Union, and propose measures that can be adopted from Ukrainian legislation to enhance personal data protection during the use of targeted advertising.[Methodology/Approach/Design] The analysis and synthesis method facilitated the examination of the essence of advertising and targeted advertising. Also, this method was used to characterize the different types of targeted advertising. The formal-legal and comparative-legal methods were utilized to analyze the norms of the European Union related to the protection of personal data. Lastly, the scenario method was employed to propose measures that could be adopted from Ukrainian legislation to enhance personal data protection during the use of targeted advertising. These methodological choices aimed to provide a comprehensive and well-founded analysis of targeted advertising and the protection of personal data within the context of aligning Ukrainian legislation with European Union requirements.[Findings] Ensuring the protection of personal data during targeted advertising involves adhering to specific rules and principles. These include ensuring that the collection of information is done in a transparent and voluntary manner. Only relevant and necessary information should be collected, and it is important to guarantee the protection of the data once it has been obtained.